An experimental study of the effects of fuel properties on reactive spray evolution using Primary Reference Fuels. (1st January 2016) - Pastor, J.V.; García-Oliver, J.M.; López, J.J.; Vera-Tudela, W.
Highlights: Six different binary blends of PRFuels were tested under different conditions. Spray penetration, lift-off length, ignition delay and soot radiation were measured. Ignition time and lift-off length were increased with increasing iso-octane. A momentum-controlled scaling law for stabilized flame length was validated. Abstract: An experimental study on the ignition and combustion of diesel-type sprays using n -heptane, iso -octane and four intermediate blends is presented. The choice of components was done in order to represent the transition from conventional diesel fuel ( n -heptane) to a gasoline-like one ( iso -octane) in terms of ignition behavior. The experiments have been carried out in a high pressure high temperature vessel using specifications from the Engine Combustion Network (ECN). Parametric variations of oxygen concentration and air temperature have been performed for each fuel. In order to investigate the spray development, schlieren imaging for the quantification of spray penetration and ignition delay, OH ∗ chemiluminescence imaging for the lift-off length, and broadband radiation imaging for the soot intensity and flame length have been applied. The results show the large effect of mixture reactivity on the ignition times and lift-off length values. Regarding the effect of the octane number of the blends on the ignition delay times, a linear effect has been found in the lower half of the blend range, while an exponential trend is evident in the top one. On the other hand, a scaling law for the stabilized flame length based upon momentum-controlled assumptions has shown that results are comparable to those obtained in the literature. Finally, the applicability of the results obtained on the performance and efficiency in real engines is discussed.